Localization principle of the spectral expansions of distributions connected with Schodinger operator. - Ahmedov, Anvarjon; Rakhimov, Abdumalik; Zainuddin, Hishamuddin (2011)
In this paper the localization properties of the spectral expansions of distributions related to the self adjoint extension of the Schrodinger operator are investigated. Spectral decompositions of the distributions and some classes of distributions are defined. Estimations for Riesz means of the spectral decompositions of the distributions in the norm of the Sobolev classes with negative order are obtained.